(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This article explores the enlightening and reformative activities of G’ozi Yunus, one of the prominent representatives of the Jadid movement in Turkestan. G’ozi Yunus, like other Jadid intellectuals such as Mahmudhoja Behbudi, Fitrat, and Munavvarqori, devoted his life to awakening the nation from ignorance, promoting modern education, and purifying Islam from superstitions and outdated traditions. His poetry and prose, especially works like “Eski maktablar haqinda” and “Al-Ulamo varasatul anbiyo”, emphasize the need for new-style schools and call upon religious scholars to fulfill their role in guiding society not only spiritually but also culturally and intellectually. G’ozi Yunus advocated for unity, enlightenment, and rational thinking, showing that religious leaders should act as heirs of prophets by serving the nation and preserving its dignity. His philosophical and educational ideas remain significant in the context of modern social and cultural challenges.